ACR20 AND ACR50 CRITERIA FOR THE ASSESSMENT OF TREATMENT RESPONSE IN PATIENTS WITH RHEUMATOID ARTHRITIS TREATED WITH METHOTREXATE - Irena Kafedjiska; Filip Guchev; Snezhana Mishevska Percinkova; Emilija Sandevska; Maja Bojadjioska; Baskim Osmani (Македонско лекарско друштво = Macedonian Medical Association, 2019)
Introduction. Multiple comparative studies have assessed the therapeutic effect of methotrexate (MTX) and have shown that it is the leading disease modifying anti-rheumatic drug (DMARD) in the treatment of rheumatoid arthritis (RA). A quantitative appraisal of the therapeutic response of this drug in a set period of time is of great importance. Aim. To make an assessment of the therapeutic response to MTX, by using the American College of Rheumatologists (ACR), ACR20 and ACR50 criteria, for a fixed time period, in patients with rheumatoid arthritis and long disease evolution. Methods. In this prospective study we examined 60 patients with RA, of which 30 with disease evolution less than one year (average disease duration 5.1+/-2.8 months, 2-11 months), and 30 with disease duration over 5 years (average disease duration 7.9+/-1.8 years, 5-12 years). They were treated with an average dose of 7.5mg MTX weekly and non-steroid anti-inflammatory drugs (NSAID) as needed. In patients with early RA, MTX was used for the first time. At baseline all patients had active disease. ACR20 and ACR50 were assessed in all patients for the duration of the study. Results. After one year 26 (86.7%) of patients with early RA had satisfied ACR20 criteria compared to 18 (62.1%) of the patients with late arthritis. After two years this changed to 25 (83.3%) vs. 20 (69%) patients, respectively. ACR50 criteria after one year of treatment were satisfied in 12 (40%) patients with early arthritis and 8 (27.6%) with late arthritis, over 5 years of disease evolution. After two years data showed 21 (70%) vs. 10 (34.5%) patients, respectively. Conclusion. Early application of MTX in patients with arthritis allows for significantly better improvement in patients with RA compared to the use of the same treatment in those with a longer evolution of the disease.
ACR20 И ACR50 КРИТЕРИУМИ ЗА ПРОЦЕНКА НА ТЕРАПИСКИ ОДГОВОР ОД МЕТОТРЕКСАТ КАЈ ПАЦИЕНТИ СО РЕВМАТОИДЕН АРТРИТИС
Keywords: rheumatoid arthritis; methotrexate; ACR20 criteria; ACR50 citeria